Premature senescence and cellular phenotype transformation of mesangial cells induced by TGF-B1. (September 2013) - Fu, Rong-Guo; Wu, Juan-Juan; Xue, Rong-Liang; Zhang, Tao; Wang, Li; Wu, Xi-Li; Duan, Zhao-Yang; Jia, Li-Ning; Ma, Li-Qun; Du, Yan; Wei, Lin-Ting
Abstract Background: Transforming growth factor-β1 (TGF-β1) is a polypeptide member of the transforming growth factor β superfamily of cytokines and performs many cellular functions. Its overexpression may lead to renal fibrosis. Aim: This study planed to investigate the effects of TGF-β1 on the cell cycle and phenotype of mesangial cells. Methods: Rat mesangial cells were cultured together with different concentrations (0, 1, 2, 5, and 10 ng/mL) of TGF-β1 for specified times from 0 min to 72 h. 0 ng/mL TGF-β1 and 0 min served as controls. Cell cycles were assessed by flow cytometry and α-smooth muscle actin expression (α-SMA) protein expression by western blot analysis. All data were presented as Mean ± SD. Statistical analysis was performed by using one-way analysis of variance and correlation analysis. Results were considered significant at p < 0.05. Results: After 15 min of co-culture with different concentrations of TGF-β1, the percentage of mesangial cells in G0/G1 phase was significantly elevated compared to the control (p < 0.05). 12 h co-culture induced cell hyperplasia, 24 h co-culture obvious up-regulation of α-SMA (p < 0.01) and one or two cells' myofibroblast phenotype transition, and 36 h co-culture several cells' phenotype transition. Correlation analysis prompted that the TGF-β1-induced premature aging was time-dependent (p < 0.01). Conclusion: TGF-β1 may induce mesangial cells' premature senescence and myofibroblast-like phenotype transformation time-dependently, which may contribute to the development of early stage of glomerulosclerosis.